Proceso de documentación e implementación de la norma NTS 002 TS en el Hotel San Martin Armenia (2016)
This project provides the accompaniment in the documentation process and implementation of the requirements of sectoral technical standard NTS TS 002 version 2014 at the San Martin Armenia, it is issued by the ministry of commerce, industry and tourism in conjunction with the power to management of tourist and hotel companies in the externship university of Colombia, in order to establish standards that promote sustainability in destinations or providing tourist services, according to resolution 2804 of 2014 ruled that the updating of the national register of tourism it is conditional upon the certification of tourism operations, giving a period of 18 months for compliance. Such specific standard requirements of environmental, economic and sociocultural sustainability, which accommodation establishments and housing (EAH) meet in pursuit of achieving certification in quality tourism, this in order to achieve in the organization better use of the good practices and thus adopt the standard as a vision in its organizational structure, and be instrumental in these businesses, thus they can use sustainability to avoid compromising future needs, finding a balance between quality of service and respect for the environment. Management systems for sustainability in hotels possible to improve their competitiveness in the hospitality sector in the region, involving all stakeholders surrounding it. Through the approach of manuals, programs, procedures, tools which will be applied to the hotel San Martin Armenia, 100% compliance with the requirements of the standard in order to achieve certification by Icontec be sought.